Support and assessment for fall emergency referrals (SAFER 2) research protocol: cluster randomised trial of the clinical and cost effectiveness of new protocols for emergency ambulance paramedics to assess and refer to appropriate community-based care. Issue 6 (12th November 2012) - Snooks, Helen; Anthony, Rebecca; Chatters, Robin; Cheung, Wai-Yee; Dale, Jeremy; Donohoe, Rachael; Gaze, Sarah; Halter, Mary; Koniotou, Marina; Logan, Phillippa; Lyons, Ronan; Mason, Suzanne; et al.
Abstract : Introduction: Emergency calls to ambulance services are frequent for older people who have fallen, but ambulance crews often leave patients at the scene without ongoing care. Evidence shows that when left at home with no further support older people often experience subsequent falls which result in injury and emergency-department attendances. SAFER 2 is an evaluation of a new clinical protocol which allows paramedics to assess and refer older people who have fallen, and do not need hospital care, to community-based falls services. In this protocol paper, we report methods and progress during trial implementation. SAFER 2 is recruiting patients through three ambulance services. A successful trial will provide robust evidence about the value of this new model of care, and enable ambulance services to use resources efficiently. Design: Pragmatic cluster randomised trial. Methods and analysis: We randomly allocated 25 participating ambulance stations (clusters) in three services to intervention or control group. Intervention paramedics received training and clinical protocols for assessing and referring older people who have fallen to community-based falls services when appropriate, while control paramedics deliver care as usual. Patients are eligible for the trial if they are aged 65 or over; resident in a participating falls service catchment area; and attended by a trial paramedic following an emergency call coded as a fall without priority symptoms. The principal outcome is the rate of further emergency contacts (or death), for any cause and for falls. Secondary outcomes include further falls, health-related quality of life, 'fear of falling', patient satisfaction reported by participants through postal questionnaires at 1 and 6 months, and quality and pathways of care at the index incident. We shall compare National Health Service (NHS) and patient/carer costs between intervention and control groups and estimate quality-adjusted life years (QALYs) gained from the intervention and thus incremental cost per QALY. We shall estimate wider system effects on key-performance indicators. We shall interview 60 intervention patients, and conduct focus groups with contributing NHS staff to explore their experiences of the assessment and referral service. We shall analyse quantitative trial data by 'treatment allocated'; and qualitative data using content analysis. Ethics and dissemination: The Research Ethics Committee for Wales gave ethical approval and each participating centre gave NHS Research and Development approval. We shall disseminate study findings through peer-reviewed publications and conference presentations. Trial Registration: ISRCTN 60481756